Silent Narrative: an Entry to the 1987 Steedman Competition - Raymond Streeter (Oz, 1987)
The setting for this project is a large, 20th Century mercantile building in a major American city. A society of architects has acquired a comer space on the ground floor where they wish to accommodate lecture facilties, a gallery and a library. The desire is to provide a center for the Society for greater influence through education and example.